Hungary : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper on Hungary reports that the public enterprises may pose significant fiscal risks on account of their quasi-fiscal activities and contingent liabilities. More than 85 percent of the economy is in private hands. According to the Privatization Act, assets may remain in long-term state ownership if they belong to a national public utility provider or are considered to be of strategic importance for the national economy or defense. Capital-intensive and labor-intensive enterprises remain as state property.